Antioxidants and characterization of stability and organoleptic properties of cocoa facial mask - Abd Gani, Siti Salwa; Abd Halim, Alyaa Nurathirah; Zaidan, Uswatun Hasanah; Halmi, Mohd Izuan Effendi; Abdul Wahab, Norliza (World Scientific Publishing, 2021)
Beauty products plant based are getting increasing interest from users and the cosmetic industry. Cocoa liquor is a natural source of antioxidants from (Theobrama cacao L.) cocoa beans, with potential health benefits. The present study was conducted to determine the stability of cocoa facial mask in different temperature, the durability of CFM in extreme high and low temperature and the prospect of integrating CFM offers additional skin defence capability by eliminating free radicals from the environment. CFM shown stabled with different storage conditions. The amount of ferric ion reducing power (FRAP) in CFM was evaluated by the reduction of ferric-TPTZ to blue ferrous-TPTZ color, while β-carotene linoleate bleaching (β-CB) assay were determined by using β-carotene emulsion. FRAP and β- carotene recorded values of 252.31 ± 0.001 mmol Fe2+/g and 83.42 ± 0.03%, respectively. The EC50 of β-carotene linoleate bleaching (β-CB) reported at 2.92 ± 0.03 mg/mL. The results suggest that CFM is a potential source of phytochemicals. The study presents scientific validation on its phytochemical contents showing presence of bioactive compounds with nutritional and therapeutic values which may have positive impact on skin health and suggesting its prospective use in value-added products such as skin care cosmetics.